Allir fuglar fljúga í ljósið - Auður Jónsdóttir 1973- (Bjartur, 2021)
The main character in this novel by critically acclaimed author Auður Jónsdóttir is Björt and she is a wanderer by nature. She wanders around Reykjavík, pays close attention to people and makes frequent notes. But her routine is broken and shattered when she is introduced to Ólöf Brá.